Exemplo de vulcanismo tardio em Portugal- rocha ígnea post-Miocénico inferior (Figueira-Algarve) - Coelho, A. V. Pinto (2008)
A small outcrop of an igneous rock (basanite) was observed in 1971 at Figueira-Mexilhoeira Grande-Algarve, enclosed by Miocene limestone and showing clear evidente of low grade thermal effects along the contact with the igneous mass. This is in agreement with F. L. Pereira Sousa who was the first geologist to admit (1917) the existence of Miocene igneous rocks in Algarve although subsequently they were not possible to localize. This work reports studies on petrography and chemical composition of this basanite and describes the evidence of the thermal effects upon the surrounding calcareous rocks. This well localized small outcrop represents an igneous rock more modern than the basaltic complex of Lisbon, hitherto assigned to the Eocene in age and recently ascribed to the Upper Cretaceous and until now considered the most recent manifestation of volcanic activity in Portugal. However this does not exclude the possibility of existence of even more modem igneous rocks in Algarve region.